PENERAPAN METODE QUALITY FUNCTION DEPLOYMENT (QFD) SEBAGAI UPAYA UNTUK PENINGKATAN KUALITAS PELAYANAN - Indriani, Sri; Sari, Sanny Andjar (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2011)
Quality of service is a very important factor in an entertainment business. This cases on research of MGM City Club is an entertainment business to the concept of One Stop Entertainment. Includes art galleries, Pub, Lounge, and karaoke.This study aims to analyze the quality of customer services and factors-other factors that can enhance pro-gress for the company. Fulfilling customer expectations and customer satisfaction will bring benefits to the company. To meet consumer expectations, it is necessary to perform design services with quality improvement QFD. The use of these methods can help com-panies focus on improvements that should be made to meet these consumer expecta-tions.Based on this analysis it is known that the highest attribute value of interest rate is